2015
DOI: 10.1002/jrs.4786
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anthocyanins in plant sources and textiles by surface-enhanced Raman spectroscopy (SERS)

Abstract: The aim of the present study was to provide experimental procedures for the identification of anthocyanin‐based dyes used in antiquity. In particular, we assessed the possibility to identify anthocyanins, both in plant extracts and in dyed textiles, by means of surface‐enhanced Raman spectroscopy (SERS), a very chemically specific technique that is moreover sensitive to the changes in structures of molecules, phenomena that occur extensively in the chemistry of anthocyanins. The choice of the plant sources (bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
0
16
2
Order By: Relevance
“…Also, it is noteworthy that the SER spectra of both blue and purple extracts differ significantly from those reported by Zaffino et al . in their characterization of anthocyanins from plant sources.…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…Also, it is noteworthy that the SER spectra of both blue and purple extracts differ significantly from those reported by Zaffino et al . in their characterization of anthocyanins from plant sources.…”
Section: Resultscontrasting
confidence: 66%
“…Also, it is noteworthy that the SER spectra of both blue and purple extracts differ significantly from those reported by Zaffino et al [36] in their characterization of anthocyanins from plant sources. In the past, some authors hypothesized that the main constituents of folium could be anthocyanins, [37] but our results compared with those of Zaffino et al seem to exclude this hypothesis.…”
Section: Ser Examination Of Extracts From Blue and Purple Pericarpscontrasting
confidence: 64%
See 1 more Smart Citation
“…This same author and co‐workers reported the use of online coupling of HPLC with SERS for the identification of historical dyes. Examples were presented of some of the colourants most widely used in history, such as morin and luteolin for yellow dyes, alizarin, purpurin, laccaic, kermesic, and carminic acids for red ones, and indigotin for blue tints . Zhou et al reported using Raman and SERS on horns and their correlation with biomechanical properties.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…Examples were presented of some of the colourants most widely used in history, such as morin and luteolin for yellow dyes, alizarin, purpurin, laccaic, kermesic, and carminic acids for red ones, and indigotin for blue tints. [46] Zhou et al reported using Raman and SERS on horns and their correlation with biomechanical properties. SERS measurements verified that the main constituents of the degradation products from both buffalo and sheep horns were amino acids and polypeptides, suggesting that these horns are suitable candidates for biomaterial scaffolds.…”
Section: Theoretical Aspects Of Sers Enhancementmentioning
confidence: 99%